BIOMASS ESTIMATION AND EFFECT OF METEOROLOGICAL PARAMETERS ON PENAEUS MERGUIENSIS STOCKS IN THE HORMUZGAN PROVINCE COASTAL WATERS - M. Safaei; E. Kamrani; M. Momeni (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2004)
This study designed with objective on shrimp population structure biomass, management aspects and meterological factors that affect on them. This investigation was carried out monthy by swept area method from Bandar Abbas to Sirik area waters. The optimum time for opening fishing season in Hormuzgan province waters in years 1999,2000, 2001 and 2002 respectively were about 9/10/1999, 4/10/2000, 2/10/2001, 28/9/2002 and total biomass for years 1999 up to 2002 were 731, 1350, 636 and 1708 tonnes, respectively. The Pearson corrlation test between catch per unit of effort (CPUE) and meteorological parameters showed the significant corrlation for mean temperature and moisture (P < 0.05) and for rainfall and evaporation did not show any significant corrlation.